Butchery & sausage-making for dummies - Harrison, Tia (New Jersey : Wiley, 2013)
This book provides information about how to butcher poultry, rabbit, beef, pork, lamb, and goats, make high-quality, preservative-free sausages, and preserve meat through curing and smoking. Tips and recipes for home cooks are also provided.
Time to meet your meat! -- Poultry, rabbit, and lamb butchery -- Pork butchery -- Beef butchery -- Sausage-making and using the whole animal -- The part of tens.
Includes index.
Keywords: MEAT CUTTING